Multidimensional evaluation of the impacts of agricultural interventions to achieve food security in Malawi - Chikafa, Mervis; Nejadhashemi, A. Pouyan; Moller, Kieron; Razavi, Hoda; Bizimana, Jean‐Claude (Food and energy security, 2023)
Malawi's food and nutrition security heavily relies on rainfed agricultural production, which is prone to the effects of climate change, such as floods and dry spells. To improve the situation, policies have been established as a guide to assist in the implementation of agricultural technologies in the country. This study aims to evaluate the effect of two national policies on addressing nutrition, economics, and food security by introducing modern/existing technologies in the Phalombe district in Malawi. To gain insight into the representative farm operations, financial, demographic, and consumption behaviors of smallholder farmers, the data were obtained through a combination of focus group discussions, expert opinions, and various published reports, including both government and nongovernment sources. The farm simulation model (FARMSIM) was utilized to analyze district‐level crop and livestock farm operations. In this study, four irrigation technologies (treadle pump system, motorized pump system, solar‐powered system, and river diversion irrigation system) were assessed among the agricultural interventions implemented in Malawi. Also, seven land uses (i.e., corn, onion, bean, rice, tomato, leafy vegetable, and cabbage) were developed and simulated under irrigation scenarios. The irrigation systems and land use scenarios were evaluated based on economics, productivity, nutrition, and risk. The treadle pump and leafy vegetable scenario were generally identified as the most preferred combination. In addition, the productivity and riskiness of the other scenarios can be improved by selecting the best combination of crop and irrigation systems. The study concludes that government and private investment in subsidies for large‐scale irrigation systems, as well as improvements to market prices and infrastructure, are necessary to boost food security and enhance the livelihood of smallholder farmers in rural Malawi. Malawi's food security is threatened by climate change. The study evaluated the effect of two national policies on addressing nutrition, economics, and food security. The study found that government and private investment in irrigation systems is necessary to boost food security.